PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MEMBANGUN EKONOMI KREATIF DI ERA DIGITAL DI KECAMATAN AIR BATU KABUPATEN BANYUASIN - Pahalmas, Juniior Zamrud; Pratiwi, Diany Putri; Aulia, Shinta Dea; Zahara, Atina (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2024)
This research aims to develop the use of applications on various digital platforms in buildingcreative businesses as an effort to increase creative human resources and have a competitive advantagein Air Batu Village, Talang Kelapa District, Banyuasin Regency. This research uses a qualitativeapproach with the aim of looking at the relationship between the use of information andcommunication technology in building a creative economy in the digital era, especially in the use ofsmartphone applications to increase the income of Micro, Small and Medium Units (MSMEs) as aneconomic mode for the residents of Air Batu Village, in Talang Kelapa District, Banyuasin Regency,South Sumatra. The relationship between the role of applications on smartphones and increasing MSMEincome in Air Batu Village was researched based on Information and Communication Technology theoryand Creative Economy theory. From the analysis carried out, findings in the field can be obtained that the vast Air Batu Village which has various business units has many good profit niches in increasinghousehold income and reducing unemployment through the MSMEs that are run, but there is still notenough education and motivation and innovation in society so that it does not reach its maximum pointin carrying out the technical use of information communication technology available on smartphones,namely online marketing communications and other advantages of social media.